The TONA model: A new methodology for assessing the development and maturity life cycles of family owned enterprises - Júlia Tobak; András Nábrádi (Journal of Innovation & Knowledge (JIK), 2020)
Understanding the operation of family businesses is important worldwide. It is worth examining and evaluating this kind of business in terms of the family, the business and the ownership dimensions. There are no research findings known to provide an international and aggregated cross-sector analysis of family businesses. The purpose of this theoretical approach is to present a new method. With this method it would be possible to carry out a cross-sector and international comparative statistical analysis of family enterprises. This is suitable for making an aggregated analysis of one or more companies. The simultaneous or separate examination of the development of dimensions can assist family businesses in measuring their own status. The TONA model is applicable to measuring the evolution of family businesses and can show the differences between sectors or countries in an illustrative way.
Keywords: 650; Cross-sector analysis; Evaluating dimensions; International comparative analysis; TONA model